Position matching between the visual fields in strabismus - Hussain, Zahra; Astle, Andrew T.; Webb, Ben S.; McGraw, Paul V. (Association for Research in Vision and Ophthalmology, 2018)
The misalignment of visual input in strabismus disrupts positional judgments.We measured positional accuracy in the extrafoveal visual field (18–78 eccentricity) of a large group of strabismic subjects and a normal control group to identify positional distortions associated with the direction of strabismus. Subjects performed a free localization task in which targets were matched in opposite hemifields whilst fixating on a central cross. The constant horizontal error of each response was taken as a measure of accuracy, in addition to radial and angular error. In monocular conditions, all stimuli were viewed by one eye; thus, the error reflected spatial bias. In dichoptic conditions, the targets were seen by separate eyes; thus, the error reflected the perceived stimulus shift produced by ocular misalignment in addition to spatial bias. In both viewing conditions, both groups showed reliable overand underestimations of visual field position, here termed a compression of response coordinates. The normal group showed compression in the left periphery, regardless of eye of stimulation. The strabismic group showed a visual field-specific compression that was clearly associated with direction of strabismus. The variation in perceived shift of strabismic subjects was largely accounted for by the biases present in monocular viewing, suggesting that binocular correspondence was uniform in the tested region. The asymmetric strabismic compression could not be reproduced in normal subjects through prism viewing, and its presence across viewing conditions suggests a hemifield-specific change in spatial coding induced by long-standing ocular misalignment.